HADITH HEARING AIDS FOR KURDISH SCHOLARS DURING THE HAJJ SEASONS BETWEEN THE TWO CENTURIES (8-9 AH/14-15 AD) - Hamid, Zemar; Rasheed, Zhiyan (Humanities Journal of University of Zakho, 2025)
The Kurdish students and scholars hearing of the Hadith during the Hajj seasons has a great role in the development of scientific life in the Two Holy Mosques of Mecca and Medina, because annually large groups of famous scholars and sheikhs in the Islamic world meet in Mecca and Medina during the Hajj seasons and there they hold scientific sessions, especially sessions for hearing the Noble Prophetic Hadith. For this reason, the Hajj seasons were a golden opportunity for students and scholars of Hadith science, and Kurdish students and scholars used to come to the Hajj seasons for religious and scientific purposes, especially between the 8th and 9th centuries AH/14th and 15th centuries AD. We must point out that after the 6th century (AH/12th century AD), students of Hadith in general and the Kurds in particular headed to Egypt and the Hijaz instead of Baghdad and the Levant, due to prevailing political situations. As for the Kurdish scholars, most of them were those who resided in Mecca and Medina. The sessions of listening to the Prophet’s hadith were held continuously in the two holy mosques, especially during the Hajj seasons. The Kurdish scholars did not only participate in these sessions, but some of them held these sessions in the two holy mosques and played a major and effective role. Kurdish women also participated in these sessions.